Critical Contextual Aspects of a Highly Complex Hospital [Aspectos Críticos Contextuais de Um Hospital de Alta Complexidade] [Aspectos Críticos Contextuales de Un Hospital de Alta Complejidad] - Torres-Canales, a (Organizacion Panamericana de la Salud, 2017)
This article presents the partial results of a SWOT analysis at the National Chest Institute, in order to generate information on critical issues affecting the strategic management of a public hospital of high complexity, and open an ethical reflection on such processes. For their determination were used: focus groups, interviews, proposed by the management team of the Hospital and discussions on the contextual level. The Individual and group interviews lasted about an hour and twenty minutes and were performed at hospital units. The conceptualization of the data was made from Grounded Theory. The study shows, according to the perception of the interviewees, their contextual issues such as rules, stakeholders and cultural country, whose ethical tension with the organization, affect the work of the National Chest Institute as a high complexity public hospital. © 2017, Organizacion Panamericana de la Salud. All rights reserved.